Integrating technology in psychological skills training for performance optimization in elite athletes: A systematic review - Siekanska, M.; Bondar, R. Z.; di Fronso, S.; Blecharz, J.; Bertollo, M. (Psychology of Sport and Exercise, 2021)
Objectives The aim of the current study was to systematically review the literature on the integration of technology in psychological skills training (PST) to optimize elite athletes` performance.